The Influence of Lifestyle, Quality, Brand Image and Prices on Converse Shoes Purchase Decisions: Gender and Education as Moderating Variables - Gandhi, Novi Chesia Puspa; Andadari, Roos Kitties (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of lifestyle, product quality, brand image and price on buying decisions of Converse shoes with gender and education as moderating variables. The data collection technique used a questionnaire with purposive sampling method and used a research sample of 210 respondents. The analysis in this study uses the SPSS program. The results of this study found that lifestyle has no effect on buying decisions for Converse shoes. Meanwhile quality, brand image and price have a significant positive effect on buying decisions for Converse shoes. The results of this study found that lifestyle has no effect on buying decisions for Converse shoes. Meanwhile, quality, brand image and price have a significant positive effect on buying decisions for Converse shoes. Gender as a moderating variable is only able to strengthen the relationship of the brand image variable to the buying decision of Converse Shoes. While education as a moderation is not able to strengthen the relationship between lifestyle, product quality, brand image and price on the buying decision of Converse Shoes.